PROBLEMS OF LEGAL DEFINITION OF LEGAL DEFINITIONS OF CORRUPTION CRIMINAL OFFENSES: SOME THEORETICAL AND LAW ENFORCEMENT ASPECTS - Лисько, Тетяна Давидівна; Рєпкіна, Юлія Євгенівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: to research the main theoretical and legally enforceable problems of legal determination of legal definitions, which are used to form compositions of corruption criminal offences. Methods: formal legal method, which gave opportunity to classify and systematize the criminal legal norms, which are researched and method of interpretation (explanation), which gave opportunity to find out the content of certain norms of criminal law. Results: as a result of made research the main theoretical and legally enforceable problems were formed and the ways of solving certain of them were suggested. Discussion: in the article certain theoretical and practical aspects of legal determination of certain definitions of corruption legal offences are submitted for discussion. Considerable gaps in current legislation in the sphere of regulation of social relations with «corrupted element» affect on the state of fight against corruption criminal offences, they make considerable differences in the explanation of the CC, which have to correspond the principle of legal certainty and terminological accuracy. Terminological problems could be solved with the help of a unified approach to determine definitions and the system of corruption offences. Gaps, relating to qualifications of corruption criminal offences have to be terminated with the help of making certain specification in the current CC of Ukraine, in particular, to the Note to Art. 364 of the Criminal Code, in particular, on the definition of «significant harm» and «grave consequences», «subject of a criminal offence». Moreover, approaches to defining a special subject of a corruption criminal offence by determining clear legal landmarks, which gave an opportunity to classify these subjects without difficulties and clearly indicate that they belong to one or another category of special subjects of corruption offences, have to be looked over carefully. Solving issues, which are outlined in this research, give an opportunity to terminate difficult problems and gaps of the current legislation in the part of determining criminal liability for corruption criminal offences.